Prevalence of cardiovascular disease in subjects hospitalized due to chronic obstructive pulmonary disease in Beijing from 2000 to 2010 - Hua, Cui; Dong-Mei, Miao; Zhi-Min, Wei; Jian-Fang, Cai; Yi, Li; Ai-Min, Liu; Fan, Li (Journal of geriatric cardiology : JGC, 2012)
Objectives To investigate the overall prevalence of cardiovascular disease （CVD） in subjects hospitalized for chronic obstructive pulmonary disease （COPD）,and explore the prevalence of the major CVD complications and trends in patients with COPD over a 10-year period.Methods Medical records in the PLA General Hospital,Beijing Union Medical College Hospital,and Beijing Hospital from 2000/01/01 to 2010/03/03 were retrospectively reviewed.A total of 4960 patients with COPD were reviewed in the study （3570 males,mean age,72.2 ± 10.5 years; 1390 females,mean age,72.0 ± 10.4 years）.Results The prevalence of CVD in COPD patients was 51.7％.The three most prevalent CVDs were ischemic heart disease （28.9％）,heart failure （19.6％）,and arrhythmia （12.6％）.During the 10-year study period,the prevalence of various CVDs in COPD patients showed a gradual increasing trend with increasing age.There was higher morbidity due to ischemic heart disease （P ＜ 0.01） in male COPD patients than in the female counterparts.However,heart failure （P ＜ 0.01）and hypertension （P ＜ 0.01） occurred less frequently in male COPD patients than in female COPD patients.Furthermore,the prevalence of ischemic heart disease decreased year by year.In addition to heart failure,various types of CVD complications in COPD patients tended to occur in younger subjects.The prevalence of all major types of CVD in women tended to increase year by year.Conclusions The prevalence of CVD in patients hospitalized for COPD in Beijing was high.Age,sex and CVD trends,as well as life style changes,should be considered when prevention and control strategies are formulated.